Biophilia in the neighbourhood : children's connection with their nearby nature - 'Izzah Adibah binti Ismail (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2015)
This research focuses on children's connection with their natural environment by the agency of outdoor activities. It emphasises on nearby nature as a setting that triggers the children's sense of unstructured play. Outdoor activities offer children the chances to interact with nature and to nurture their sense of biophilia. Biophilia can be described as the affection for living things or nature. Thus, a positive environment for the children's development needs to consist of biophilic design in order to encourage contact with nature on a daily basis. Hence, this study aims at establishing the preferences of children in their natural environment, accompanied by an understanding of the sense of biophilia in their urban neighbourhood settings. Three objectives are formulated: (i) to examine the types of nearby nature that middle childhood children are connected with within their neighbourhood settings, (ii) to identify the children's perception of nature (preference or otherwise) and their sense of biophilia, and (iii) to determine the physical characteristics of nearby nature that connect the children to Biophilia. The scope of this study highlights on middle childhood children in an urban neighbourhood with various socio-demographic backgrounds in Taman Melati, Kuala Lumpur. Accordingly, in order to reveal the children's behaviour and thought, a mixed-method research design was conducted through questionnaire survey, semi-structured interview and observation. A review of literature was also carried out in the study. Data obtained from the data collection stage were analysed by descriptive statistics and content analysis. The finding shows that most of the children are familiar with places that are dominated by natural elements, while mixed elements of man-made and nature prevails in the preferred places. Due to children's limited independence mobility, both of the places are close-proximity to home. The familiar places afford children with unstructured activities, while the preferred places govern balanced types of children's activities. Children value the preferred places because the places make them happiest, afford a sense of privacy and rich in natural affordances. In general, children prefer mixed elements, with more inclination to the natural elements of the settings. Besides, parental restriction, availability of social interactions, structured lifestyles, accessibility and maintenance are the influential factors that influence children's opportunity to be outdoors. It is important to eliminate existing physical problems in children's environment since they usually lead to other social problems. Furthermore, the majority of them have positive views about nature. Notably, regular direct connection with nature developed children's sense of biophilia. Environmental knowledge supported by the sense of biophilia is a strong indicator for their willingness to protect the environment. In brief, the findings are valuable and useful in for designing children's environment that nurtures their sense of biophilia.